A Probabilistic Extension of Action Language ${\cal BC}$+}$. Issue 3 (10th August 2018) - LEE, JOOHYUNG; WANG, YI
Abstract: We present a probabilistic extension of action language ${\cal BC}$+$ . Just like ${\cal BC}$+$ is defined as a high-level notation of answer set programs for describing transition systems, the proposed language, which we call p ${\cal BC}$+$, is defined as a high-level notation of LP MLN programs—a probabilistic extension of answer set programs. We show how probabilistic reasoning about transition systems, such as prediction, postdiction, and planning problems, as well as probabilistic diagnosis for dynamic domains, can be modeled in p ${\cal BC}$+$ and computed using an implementation of LP MLN .